Zygaena Fabricius, 1775, images in Russian masterpieces of the 19th and 20th centuries (Lepidoptera: Zygaenidae) - Konstantin A. Efetov; Gerhard M. Tarmann (SHILAP, 2024)
Two realistic Zygaena Fabricius, 1775 images were found by the first author in the paintings of two Russian artists Vasily D. Polenov and Arkady A. Plastov representing Zygaena lonicerae (Scheven, 1777) and Zygaena ephialtes (Linnaeus, 1767) (red peucedanoid morph) respectively. Polenov also depicted Amata nigricornis (Alphéraky, 1883) with some characters of the red ephialtoid morph of Zygaena ephialtes.